2023
DOI: 10.1002/bte2.20220064
|View full text |Cite
|
Sign up to set email alerts
|

Engineering strategies of metal‐organic frameworks toward advanced batteries

Abstract: Metal‐organic frameworks (MOFs) integrate several advantages such as adjustable pore sizes, large specific surface areas, controllable geometrical morphology, and feasible surface modification. Benefiting from these appealing merits, MOFs have recently been extensively explored in the field of advanced secondary batteries. However, a systematic summarization of the specific functional units that these materials can act as in batteries as well as their related design strategies to underline their functions has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 125 publications
0
12
0
Order By: Relevance
“…As the research progressed, researchers found that the morphology of the active material also greatly influenced the corresponding electrochemical properties. 132 Accordingly, a variety of morphology designs were gradually developed by researchers.…”
Section: Strategies Of Pbasmentioning
confidence: 99%
“…As the research progressed, researchers found that the morphology of the active material also greatly influenced the corresponding electrochemical properties. 132 Accordingly, a variety of morphology designs were gradually developed by researchers.…”
Section: Strategies Of Pbasmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) have drawn research interest in numerous elds such as catalysis, sensing, [14][15][16] supercapacitors, 17,18 and metal-ion batteries 19 because of their unique features of large surface area, controllable pores, and tunability in structure as they are composed of metal ion/cluster centers and organic ligands. [20][21][22] It is considered that their unique structure can allow for the access of electron/ion into the framework structure, thus guaranteeing the high energy storage ability of the material. 23,24 In particular, Ni/Co-based MOFs display outstanding energy storage capability due to rich redox reactions and electrolyte transport channels, which enable a fast charge transfer rate.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Exciting breakthroughs are still anticipated in overcoming these obstacles. [27,28] On the other hand, halogen (Cl 2 , Br 2 , and I 2 ) based cathodes utilizing conversion reactions exhibit comparable redox potentials (Figure 1a) and significantly lower costs, enabling aqueous zinc-halide batteries (AZHBs) become promising candidates in EES devices. [29,30] Note that fluorine in its elemental form is a highly toxic and corrosive gas, and due to its natural state being gaseous, it poses significant challenges as a cathode.…”
Section: Introductionmentioning
confidence: 99%